PROVARIANS: Product Variation Management System untuk Menciptakan Pasar UMKM yang Sehat pada Kampung Wisata Blekok - Januar Adi Putra; Fahrobby Adnan; Panca Oktawirani; Yeni Puspita (Jurnal Mitra Pengabdian Farmasi, 2023)
The Blekok Tourism Village is the main source of income for the people of Klatakan village. Many MSMEs and homestays in Blekok Village are owned by local residents and are a source of income for their residents, besides that there are also many handicraft businesses made from shells and wood which are managed independently by residents under the assistance of Pokdarwis of Blekok Village. Currently, the SMEs that are affiliated in Blekok Tourism Village have not been properly regulated, as have the products being marketed. Disputes often occur between MSMEs in Blekok Tourism Village due to the presence of similar products at different prices. This problem causes price wars between SMEs and unhealthy competition. Another problem that occurs is that tourism managers sometimes do not know about the distribution of the number, type, price and quality of products marketed in Blekok Tourism Village, this causes the quality of superior product management to be less than optimal which can also cause a decrease in tourist interest in visiting. Blekok Tourism Village. Based on the problems that have been described, the service team will continue the activities in this 2nd year by proposing a digital technology innovation called PROVARIANS.